A Series of Discrete Dichloride Dihydrates: Characterisation and Symmetry Effects. Issue 10 (8th September 2020) - Senthooran, Rathiga; Curnow, Owen J.; Brenner, Thomas; Weiss, Robert; Ferreras, Manuel; Crittenden, Deborah L.
Abstract: A series of three discrete dichloride dihydrates [Cl2 (H2 O)2 ] 2− have been isolated with different triaminocyclopropenium (TAC) cations and with different crystallographic symmetries. The cluster exhibits D 2h symmetry with the tris(dimethylamino)cyclopropenium cation [C3 (NMe2 )3 ] +, C 2h symmetry with the fluorinated cation [C3 (N(CH2 CF3 )2 )(NBu2 )2 ] + (containing two 2, 2, 2‐trifluoroethyl substituents) and C 2v symmetry with the more fluorinated [C3 (N(CH2 CF3 )2 )2 (NBu2 )] + cation. The effect of symmetry on the infrared spectra of the dichloride ion‐pair clusters, as well as deuterated analogues, has been investigated. The D 2h ‐ and C 2h ‐symmetric clusters each exhibit two stretching bands in the infrared at 3427 and 3368 cm −1 for D 2h symmetry and 3444 and 3392 cm −1 for C 2h symmetry, whereas the C 2v ‐symmetric cluster exhibits three bands at 3475, 3426 and 3373 cm −1 . Computational studies were carried out on a [Cl2 (H2 O)2 ] 2− cluster with C 2v symmetry to aid the infrared band assignments. Abstract : Pairing up : Discrete dichloride dihydrate ion pairs form with crystallographically‐imposed D 2h, C 2h and C 2v symmetry classes. Although there are only weak non‐classical hydrogen‐bonding interactions (mostly CH−Cl) with the cations that cause small structural variations, there are significant spectroscopic changes in the infrared stretching region.